A generalised component method for bolted angle connections. (November 2022) - Wan, Wodong; Yan, Shen; Zhang, Hao; Rasmussen, Kim J.R.
Abstract: This paper extends the existing Generalised Component Method (GCM) to model the full-range behaviours of connections with bolted angles, by introducing two new components, i.e., the slip component to model the slip of bolts (in shear), and the gap component to model the contact of beam bottom flange and column due to large joint rotation. The key aspects and principles of the extended GCM are established, including its framework, modelling techniques, and the constitutive models of the new components and other important components. The sequences of springs activation and the moment–rotation curves of individual loading stages were analysed. The extended GCM is compared against existing experimental results on three typical bolted angle connections. It is found the proposed GCM can predict the full-range moment–rotation behaviour of the connections reasonably well, showing significant improvement than the current component method in Eurocode 3 and the three-parameter-power model (3PPM). Highlights: GCM is extended to bolted angle connections. Effects of bolt slippage and beam flange contact are modelled. Extended GCM shows higher accuracy than prior models including the EC3 model.